Você está na página 1de 107

29,7

 

 

 

 

 

 

 

(P )

x,y

f (x, y)

g(x, y)

0

x X, y Y Z n y

X Y R n x R n y Y f : X × Y R g : X × Y R m f g y

(P )

x,y f (x, y)

g(x, y)

x X, y Y Z n y

0

X Y R n x R n y Y

f : X × Y R g : X × Y R m

P

P

˜

P

P

T

= {(x 1 , y 1 ),

, (x k , y k )}

T

P P

T

P

P

α

¯

( P )

α,x,y

α

f (x, y)

α

 

g(x, y)

0

x X, y Y Z n y

x, y¯) X × Y

P

f x, y¯) T x x¯

y y¯

gx, y¯) T x x¯

y y¯

+ f x, y¯)

α

+ gx, y¯)

0

x, y¯) P

T =

, (x k , y k )} k

{(x 1 , y 1 ),

P

P AE (T) α,x,y

α

f (x k , y k ) T x

y

x k

y k

g(x k , y k ) T x

y

x X, y Y Z n y

x k

y k

+ f(x k , y k )

α,

(x k ,

y k ) T

+ g(x k , y k )

0,

(x k , y k )

T

P

α, x,ˆ yˆ) αˆ = f x, yˆ) x, yˆ)

P

T (x k , y k )

(x k , y k )

T

(x k , y k ) T

= f (ˆ x, y ˆ) (ˆ x, y ˆ) P T ( x k ,

T α, x,ˆ yˆ) y P yˆ

(P yˆ )

x

f (x, yˆ) g(x, yˆ) x X

0

P yˆ x˜ x, yˆ) P f x, yˆ) x, yˆ) T P yˆ P yˆ

V

(P

yˆ

)

u,x

m

i=1 u i

g(x, yˆ)

u

u

0,

x

X, u R m

u, xˇ) P

V x, yˆ)

yˆ

T T x, yˆ)

P yˆ x, yˆ)

P yˆ P T P P f yˆ k P P T

V

yˆ

P T 0 (x ∗ , y ∗ ) P z U = +∞ z
P T 0
(x ∗ , y ∗ ) P
z U
= +∞
z L = −∞
˜
(x 0 , y 0 )
P P
T = T 0 ∪
{(x 0 , y 0 )}
k = 1
P AE (T ) P T
P yˆ y P yˆ
P
V P yˆ
z U − z L
> P AE (T )
(ˆα, x,ˆ yˆ) P AE (T)
z
L = αˆ
y
k = yˆ
P yˆ
x k P yˆ
f (x k , y k ) < z U
z U = f(x k , y k )
(x ∗ , y ∗ ) = (x k , y k )
x k P
V
T
= T ∪
(x k , y k )
k
= k + 1

P

yˆ

V

(P yˆ )

jB k

y j y j ≤ |B k | − 1

jN k

B k = {j| y

k = 1} N k = {j| y

j

k = 0} y k

j

y k (P yˆ ) y k z L z U

y P x y y x

P yˆ

P

V

yˆ

x k y k x y k K V K I

K V

K I

=

{k | P y k }

=

{k | P y k }

k K V y

α

y f(x k , y k ) T (y y k ) + f(x k , y k )

+(λ k ) T (y g(x k , y k ) T (y y k ) + g(x k , y k ))

λ k P y k x x k k K I y

0 (µ k ) T y g(x k , y k ) T (y y k ) + g(x k ,

y k )

y k k K I

µ k P

V

y

k

(P DBG )

α,y

α

α

y f(x k , y k ) T (y y k ) + f(x k , +(λ k ) T (y g(x k , y k ) T (y y k )

y k ) + g(x k , y k )),

k

K V

0

(µ k ) T (y g(x k , y k ) T (y y k ) + g(x k , y k )), y Y Z n y

k

K I

P (x ∗ , y ∗ ) P z L = −∞ K = ∅
P
(x ∗ , y ∗ ) P
z L = −∞
K
= ∅
V
K I = ∅
y 0 ∈ Y
P y 0
x 0 P y 0
K V
= {0}
z U = f(x 0 , y 0 )
(x ∗ , y ∗ ) = (x 0 , y 0 )
x 0 P F
K I = {0}
P DBG P (x i , y i )
i = 0,
, k
z U − z L > P DBG
k = k + 1
(α k , y k ) P DBG
z L = α k
P y k
x k P y k λ k
K V = K V ∪ {k}
f (x k , y k ) < z U
z U = f(x k , y k )
(x ∗ , y ∗ ) = (x k
, y k )
x k P F k µ k
K I = K I ∪ {k}
y

z

U

= +

y

0

y k

V

P yˆ P

yˆ

x,y

c T x + d T y

 

g(x, y)

0

x X,

y Y Z n y

P

x,y

c T x + d T y

g(x k , y k ) T x

y

x X, y Y Z n y

x k

y k

+ g(x k , y k )

0,

(x k , y k ) T

h(x)

˜

˜

h(x) = hx) T (x x˜) + hx) hx) =

hx)

g(x, y) 0 x, y¯)

x, y¯)

x, yˆ)

(x 0 , y 0 ) X × Y

y